(untitled) (Fiep Bulletin - online, 2014)
Psoriasis is an inflammatory, recurrent, chronic dermatosis, related to the genetic transmission, that has as consequence dermofunctional alterations , it can be treated by the physiotherapist who together with the doctor will act in the tegumentary recovery. The present study aims at an evaluatation of the effectiveness of the use of the modified sequential therapy, using ultraviolet radiation, at psoriasis, after twenty sessions of physiotherapy. The volunteer was submitted to an evaluation before the treatment, at the tenth session and at the end of the treatment, at th e twentieth session, where the lesions had been measured through paquimeter. It was noted that the employed stimulaton was capable of promoting a reduction of the injuries, improvement of the pigmentation and scalling off. With this work it was possible to acknowledge the importance of the professional physiotherapist’s action in the treatment of psoriasis, through the use of the ultraviolet radiation.